Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
That's OK, but you have not said which variable you want to solve it for.
To solve for 'x':
c + ax = dx
Subtract c from each side: ax = dx - c
Subtract dx from each side: ax - dx = -c
Factor the left side: x (a - d) = -c
Divide each side by (a - d) : x = -c / (a - d) or x = c / (d - a) .
To solve for 'c':
c + ax = dx
Subtract ax from each side and factor: c = x (d - a)
To solve for 'd':
c + ax = dx
Divide each side by 'x': d = c/x + a .
To solve for 'a':
c + ax = dx
Subtract 'c' from each side: ax = dx - c
Divide each side by 'x': a = d - c/x .
.
To solve for 'x':
c + ax = dx
Subtract c from each side: ax = dx - c
Subtract dx from each side: ax - dx = -c
Factor the left side: x (a - d) = -c
Divide each side by (a - d) : x = -c / (a - d) or x = c / (d - a) .
To solve for 'c':
c + ax = dx
Subtract ax from each side and factor: c = x (d - a)
To solve for 'd':
c + ax = dx
Divide each side by 'x': d = c/x + a .
To solve for 'a':
c + ax = dx
Subtract 'c' from each side: ax = dx - c
Divide each side by 'x': a = d - c/x .
.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.